DENGUE: WHO IS DYING IN THE STATE OF PARÁ? - LISBOA, José Luiz de Carvalho; SOUZA, Cristiane Nazaré Pamplona de; RAMOS, Edson Marcos Leal Soares; ALMEIDA, Silvia dos Santos de (Brazilian Journal of Biometrics, 2018)
In the last 50 years, the incidence of dengue grew over 30 times, with the development of the geographical expansion for new countries and currently, reaching small towns and rural areas. It is estimated about over than 50 million of infection by dengue occur annually and approximately 2.5 billion people die in countries where the disease is endemic. In the state of Pará, 4042 cases of dengue were confirmed until October 1st, 2015. At the same period in the year of 2014, 2704 occurrences were registered, which represents an increase of almost 50%. Thus, this work’s objective is to trace the patient’s with dengue profiles in the state of Pará and to verify the relationship between those patients stage of life and the type of dengue with evolution case. For this end, the descriptive analysis technique was utilized, aiming to trace the patient’s profiles confirmed with dengue. The correspondence analysis technique was utilized to verify what was (exclude) the relationship between the patients’s stage of life and the type of dengue fever with evolution case. As the main results, it was noticed that the majority of the patients are female, residing in urban zones and are adults. It was still perceived that elders, children and individuals that had dengue with complications, shock syndrome and hemorrhagic fever had the highest probabilities of dying. Therefore, it is due noticed that is important to give this disease greater attention, above all to the children and elderly stages of life, because, from the results it was evidenced that the individuals on these stages of life are the most prone to die from the disease.